Dielectric Spectroscopy for Non-Invasive Sensing of Multi-Layered Organ-on-Chip Devices - Tim Hosman; Massimo Mastrangeli; Marco Spirito (Proceedings)
Organ-on-chip (OoC) is emerging as a key technology for improved pre-clinical drug testing. Monitoring tissues and the artificial microenvironment in OoC devices is critical to recapitulate human physiology; however, sensing is often invasive, superficial, and not continuous over time. This work aims to overcome these issues by proposing dielectric spectroscopy as a non-invasive and time-continuous sensing technique capable of extracting information from multi-layer OoC devices, including distinguishable tissue layers. The presented results set the foundations for this goal by proving this technique’s feasibility, showing excellent correspondence between the experimental and modelled data, and providing design guidelines for application-tailored optimization.